2018
DOI: 10.1016/j.puhe.2017.12.007
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing seasonal influenza vaccination behaviour among elderly people: a systematic review

Abstract: This is the first systematic review to analyse the factors influencing influenza vaccination behaviour of elderly people using a framework integrating the HBM and the TRA. The framework identified key factors of influenza vaccination and presented the inter-relation of behaviour-related variables. However, further well-designed studies are required to explore the inter-relationships accurately and comprehensively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
113
1
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 123 publications
(144 citation statements)
references
References 63 publications
12
113
1
4
Order By: Relevance
“…This is in line with a recent systematic review on factors influencing flu vaccination behavior, which include previous vaccination history as one of the key factors, together with age, poor health status, medical service use, receiving knowledge/information from healthcare professionals. 32 Regarding the effectiveness on reducing the risk of death (any cause) and the risk of influenza-related hospitalization, we found that, adjusting simultaneously for other individual characteristics, influenza vaccination was significantly associated with lower mortality and influenza-related hospitalization rates, and the benefit was found for all the discharge diagnoses including, influenza, pneumonia, respiratory, and cardiovascular diseases. Moreover, repeated influenza vaccination in the previous seasons influenced positively the vaccine effectiveness in the elderly.…”
Section: Discussionmentioning
confidence: 84%
“…This is in line with a recent systematic review on factors influencing flu vaccination behavior, which include previous vaccination history as one of the key factors, together with age, poor health status, medical service use, receiving knowledge/information from healthcare professionals. 32 Regarding the effectiveness on reducing the risk of death (any cause) and the risk of influenza-related hospitalization, we found that, adjusting simultaneously for other individual characteristics, influenza vaccination was significantly associated with lower mortality and influenza-related hospitalization rates, and the benefit was found for all the discharge diagnoses including, influenza, pneumonia, respiratory, and cardiovascular diseases. Moreover, repeated influenza vaccination in the previous seasons influenced positively the vaccine effectiveness in the elderly.…”
Section: Discussionmentioning
confidence: 84%
“…Additional factors in uencing in uenza vaccination uptake by older citizens found in this analysis range from in uence of family/friend [22,26,32,42] to household arrangements/children [10,18,19,21,22,28,30,31,33,37,38,42,47,48], previous vaccinations [9, 15, 17-20, 22, 29, 30, 32, 35, 38, 42, 51] and other health parameter [9, 15-21, 25, 27, 28, 31, 35, 39]. This implies that the psychosocial environment, like in children, impacts VU.…”
Section: Discussionmentioning
confidence: 82%
“…The study designs are divided into 34 cross-sectional studies of which 13 studies were developed by means of a secondary analysis of already existing data [11, 12, 14, 15, 19-21, 28-30, 38, 39, 41] and two cross-sectional studies following a qualitative study design [26,32], four randomized controlled trials [43][44][45][46], two systematic reviews [47,48], two cohort studies [49,50] and two theoretical reviews [51,52].…”
Section: Study Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations